2021
DOI: 10.12659/ajcr.932722
|View full text |Cite
|
Sign up to set email alerts
|

D-chiro-inositol Induces Ovulation in Non-Polycystic Ovary Syndrome (PCOS), Non-Insulin-Resistant Young Women, Likely by Modulating Aromatase Expression: A Report of 2 Cases

Abstract: Case series Patients: Female, 19-year-old • Female, 23-year-old Final Diagnosis: Anovulation Symptoms: Oligomenorrhea Medication: — Clinical Procedure: — Specialty: Obstetrics and Gynecology Objective: Unknown etiology Background: Anovulation consists in the lack of oocyte release during the menstrual cycle, leading to an irregular menstrual cycle. Untreated chronic anovulation is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This study confirmed that reproductive concerns are prevalent among patients of reproductive age with breast cancer. A large number of studies [28][29][30][31][32][33][34][35][36] have been conducted on fertility preservation and fertility counselling, which are also seen as major protective factors in reproductive concern. Fertility problems after cancer treatment involve multiple disciplinary areas, including oncology, reproductive endocrinology, mental health counselling, clinical research and patients.…”
Section: The Status Of Reproductive Concernmentioning
confidence: 99%
“…This study confirmed that reproductive concerns are prevalent among patients of reproductive age with breast cancer. A large number of studies [28][29][30][31][32][33][34][35][36] have been conducted on fertility preservation and fertility counselling, which are also seen as major protective factors in reproductive concern. Fertility problems after cancer treatment involve multiple disciplinary areas, including oncology, reproductive endocrinology, mental health counselling, clinical research and patients.…”
Section: The Status Of Reproductive Concernmentioning
confidence: 99%
“…A case report [168] showed that after six weeks of supplementation with D-chiro-Ins (1200 mg/day) ovulation occurred in two young non-PCOS lean women with anovulation. Indeed, in these patients, progesterone increased from 0.5 to 12 ng/mL, accompanied by endometrial thickening and menstruation around 50 days after the start of treatment.…”
Section: D-chiro-inositol Dual Effects (Reduction In Estrogens In Estrogen-sensitive Female Disorders; Increase In Androgens In Male Hypomentioning
confidence: 99%
“…The results showed a higher fertilization rate in the ICSI group (73%) than in the C-IVF group (45%) ( 38 ). In one case, after 6 weeks of treatment with 1200 mg of d-chiro-inositol (DCI), ovulation resumed in two non-PCOS anovatory women with elevated progesterone and luteinizing hormone and endometrial thickening ( 39 ).…”
Section: Discussionmentioning
confidence: 99%